How much can people fake on the dark triad? A meta-analysis and systematic review of instructed faking. (July 2022) - Walker, Sarah A.; Double, Kit S.; Birney, Damian P.; MacCann, Carolyn
Abstract: Prior meta-analyses demonstrate that people can intentionally distort Big Five personality scores when instructed. As yet, there is no equivalent meta-analysis addressing instructed faking on the dark triad (narcissism, Machiavellianism, and psychopathy). Therefore, we review mean score changes to the dark triad domains and facets under instructed faking. Due to insufficient k for meta-analysis, narcissism and Machiavellianism were systematically reviewed alongside psychopathy. The systematic review revealed inconsistent findings for narcissism and Machiavellianism with several effects in the opposite direction than expected. The psychopathy meta-analysis showed that: (a) scores were significantly lower under fake good compared to answer honestly instructions ( d = −0.40); and (b) scores were significantly higher under fake bad compared to answer honestly instructions ( d = 1.88). Subgroup analyses revealed significant score decreases under fake good instructions for both primary ( d = −0.56) and secondary psychopathy ( d = −0.96), and a significant score increase under fake bad instructions for primary ( d = 1.69) and secondary psychopathy ( d = 1.50). We conclude that dark triad measures are fakeable to a similar extent as the Big Five, and discuss the relevance of our findings for dark triad assessment in several applied contexts. Highlights: People can significantly fake good, and bad on self-report psychopathy measures. Primary and secondary psychopathy scores decrease under fake good instructions. Primary and secondary psychopathy scores increase under fake bad instructions. People fake bad on total and vulnerable, but not grandiose narcissism. Faking scores on Machiavellianism depend on the self-report scale being used.